2021
DOI: 10.1007/s10384-021-00880-2
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral refraction in Japanese schoolchildren with low to moderate myopia

Abstract: Purpose To report the profile of peripheral refraction in Japanese children with mild to moderate myopia and compare it with reported data from other countries. Study design Cross-sectional study. Methods Subjects were 76 Japanese children with myopia (mean± SD [range] spherical equivalent, −3.04±0.98 [−0.50 to −4.50] D; mean age, 10.0±1.5 [6-12] years). We performed cycloplegic refraction using an open-field autorefractor FR-5000 (Grand Seiko) while the subject looked at external fixation targets located at 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 23 publications
4
2
0
Order By: Relevance
“…The relative peripheral refraction at 10° T, 10° N, and 20° N significantly differed between the myopic and non-myopic groups. These results are consistent with previously reported data [13][14]18] , which showed that relative peripheral hyperopia might correlate with myopia onset; however, it is unclear if this relationship is causal or merely a correlation, at least in our 2-year follow-up study. Our study showed that in all non-myopic eyes, the relative peripheral refraction only increased at 20° T in 2y, of which H0-H2 and E0-E2 subgroups had comparable variation in central refraction and a similar trend in relative peripheral refraction change.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…The relative peripheral refraction at 10° T, 10° N, and 20° N significantly differed between the myopic and non-myopic groups. These results are consistent with previously reported data [13][14]18] , which showed that relative peripheral hyperopia might correlate with myopia onset; however, it is unclear if this relationship is causal or merely a correlation, at least in our 2-year follow-up study. Our study showed that in all non-myopic eyes, the relative peripheral refraction only increased at 20° T in 2y, of which H0-H2 and E0-E2 subgroups had comparable variation in central refraction and a similar trend in relative peripheral refraction change.…”
Section: Discussionsupporting
confidence: 94%
“…Third, accommodation might also be a factor related to peripheral refraction [27][28] , and the effects of accommodation of the peripheral retina on myopia onset and progression remain to be studied. Our results here are in line with those of other studies on peripheral refraction and reveal hyperopic changes in relative peripheral refraction in children who became myopic [7,15,18,20,29] . Our findings suggested that relative peripheral hyperopia at 10° N may predict the occurrence of myopia in 14 to 16-yearold Chinese students, although the exact reason was unknown.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…One of the current hypotheses is peripheral defocus theory [36][37][38] , which have been shown in animal studies that peripheral myopic defocus could modulate not only peripheral ocular growth, but also axial growth [39] . However, recent investigations in humans have failed to find the correlation between peripheral refraction and myopia progression [40] . The peripheral myopic shift induced by ortho-k has the following characteristics: first, the range and power of the peripheral defocus across the retina caused by ortho-k remained stable, as the corneal morphology stabilizes after 1mo of ortho-k lens wear.…”
Section: Resultsmentioning
confidence: 99%
“…The magnitude of the hyperopic shift was similar to that reported in other studies. 7,[31][32][33] We found asymmetry between nasal and temporal eccentricities at the same peripheral location for each lighting condition, although the result was not significant (all p > 0.89). Marcellán et al 34 recently reported that the RPR was less hyperopic for the TVF than the NVF, but again, the difference was not statistically significant.…”
Section: Rpr Across the Visual Field For Each Lighting Conditionmentioning
confidence: 59%